Protected area management - Worboys, Graeme L. (Oxford University Press, 2005)
Protected Area Management examines the multi-disciplinary task of managing protected areas. This second edition of this authorative text has been updated, expanded and includes new Australian and international case studies. This comprehensive text is an essential text for students and an invaluable resource for practitioners and all readers who are concerned about conservation.